Assigned and Observed Difficulty of the Questions on an Academic Achievement Test (Revista Estudios Psicológicos, 2021)
Those in charge of constructing academic achievement tests propose a set of questions at three levels of difficulty: low, medium, and high. When a calibrated question bank is not available, the builders draw on their experience to estimate the problem of the questions they propose. In this way, before the application, we have a level of difficulty assigned to each test question. Subsequently, with the data collected from the response pattern of the examinees, we can obtain the difficulty index of each question. Thus, after application, we have an observed level for each question. The objective of this study is to determine the degree of coincidence between the assigned difficulty and that observed in each of the questions in an academic achievement test.
Keywords: Difficulty index; discrimination index; evaluation indicator; outfit; infit